Breathing Life Back Into the Kidney—Continuous Renal Replacement Therapy and Veno-Venous Extracorporeal Membrane Oxygenation. Issue 2 (February 2021) - Deatrick, Kristopher B.; Mazzeffi, Michael A.; Galvagno, Samuel M.; Boswell, Kimberly; Kaczoroswki, David J.; Rabinowitz, Ronald P.; Madathil, Ronson J.; Cornachione, Christopher R.; Herr, Daniel L.; Scalea, Thomas M.; Menaker, Jay
Abstract : The purpose of this study was to evaluate the incidence of continuous renal replacement therapy (CRRT) in patients supported with veno-venous extracorporeal membrane oxygenation (VV ECMO). Secondary outcomes included mortality and the need for hemodialysis on hospital discharge. We performed a retrospective cohort study of all patients admitted to a specialty unit on VV ECMO between August 2014 and August 2018. Trauma and bridge to lung transplant patients were excluded. Demographics, comorbidities, pre-ECMO, ECMO, and renal replacement therapy outcome data were collected and analyzed with parametric and nonparametric statistics as appropriate. One hundred eighty-seven patients were enrolled. Median age was 45 (32, 55) years; precannulation pH, 7.21 (7.12, 7.30); PaO2 /FiO2 ratio, 69 (56, 86); respiratory ECMO survival prediction score, 3 (0, 5); sequential organ failure assessment score, 12 (10, 14); and creatinine, 1.45 (0.93, 2.35) mg/dL. Overall survival to hospital discharge was 74.6%. Ninety-four (50.3%) patients had CRRT while on VV ECMO. Median time on CRRT was 14 (7, 21) days with 59 (61.4%) of these patients surviving to hospital discharge. Four (6.8%) patients, none with documented preexisting renal disease, required hemodialysis on discharge. CRRT patients had a statistically higher precannulation sequential organ failure assessment score, creatinine, total bilirubin and lower precannulation pH, respiratory ECMO survival prediction score, and platelet count compared with non-CRRT patients. Survival was 61.4% vs. 88.1% ( p < 0.001). More than half of our patients received CRRT while on VV ECMO. CRRT was used in a more critically ill patient population and was associated with higher in-hospital mortality. However, for patients who survived to hospital discharge, the majority have full renal recovery.